Malaysia : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Malaysia. (IMF Staff Country Reports; Country Report, 2021)
Malaysia entered the pandemic from a robust economic position but has nonetheless been significantly affected. A synchronous fiscal, monetary and financial policy response has helped cushion the economic impact. As a result, after a deep recession in 2020, and assuming the pandemic is brought under control in Malaysia and globally, growth would rebound to 6.5 percent in 2021 as supply side constraints are lifted and domestic and external demand recover. Large downside risks will remain.